Perancangan sistem informasi akuntansi penyaluran BSU di PT Bank Tabungan Negara menggunakan Micrsoft Visual Studio 2010 - Mirani, Amelia; Murti, Dias Novia; Muthmainnah, Muthmainnah; Agustin, Cahyadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
BSU is assistance given to workers or laborers during the COVID-19 pandemic. The purpose of this study was to find out the information system for channeling BSU funds at PT. State Savings Bank to BSU beneficiary customers. Information is collected using qualitative methods with a descriptive approach by means of observation and literature study. The results of research that has been done by the author at the PT. State Savings Bank (BTN) Bandung Branch With the BSU distribution accounting information system, it can be easier for officers to input, process, generate data, and check the accuracy of customer data for those who receive Wage Subsidy Assistance (BSU). At the time of data input, the officer has successfully entered data into the system, which can be processed for data checking and then processed for the storage process. The output of this system is that it displays customer data that receives wage subsidy assistance, which is then sent to customer service so that customer service no longer manually checks customer data. In addition, this BSU distribution information system has become more integrated into improving the quality of the bank.